Non-Sustained Ventricular Tachycardia Episodes Predict Future Hospitalization in ICD Recipients with Heart Failure - Uçar,Fatih Mehmet (2017)
Abstract Background: Implantable cardioverter-defibrillator (ICD) therapy is well known to reduce mortality in selected patients with heart failure (HF). Objective: To investigate whether monitored episodes of non-sustained ventricular tachycardia (NSVT) might predict future HF hospitalizations in ICD recipients with HF. Methods: We examined 104 ICD recipients (mean age: 60 ± 10.1 years, 80.8 % male) with HF who were referred to our outpatient clinic for device follow-up. After device interrogation, patients were divided into NSVT positive and negative groups. The primary endpoint was the rate of hospitalization within the next 6 months after initial ICD evaluation. Results: Device evaluation demonstrated at least one episode of monitored NSVT in 50 out of 104 patients. As expected, no device therapy (shock or anti-tachycardia) was needed for such episodes. At 6 months, 24 patients were hospitalized due to acute decompensated HF. Hospitalization rate was significantly lower in the NSVT negative as compared with positive groups (38% versus 62%; adjusted hazard ratio [HR] 0.166 ; 95% CI 0.056 to 0.492; p = 0.01). Conclusions: Monitored NSVT bouts in ICD recordings may serve as a predictor of future HF hospitalizations in ICD recipients with HF suggesting optimization of therapeutic modalities in these patients along with a close supervision in the clinical setting.